Sie sind auf Seite 1von 12

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

Solution 2 2 4x −2 ( x 1 1 )) 1 ∫ dx = 4

Solution

2 2 4x −2 ( x 1 1 )) 1 ∫ dx = 4 (
2
2
4x −2
(
x
1
1
))
1
dx = 4
(
ln 2x + 1
|
|
+ C
+ 8
(
+ 2x+1
2x+1
) 3
− 4 2x+1
(
) 2
+ 2 2x+1
(
) 2
Steps
2
4x −2
dx
3
(
2x+1
)
2
2
Hide Steps
4x −2
4x
2
Expand
:
3
3
3
(
2x+1
)
(
2x+1
)
(
2x+1
)
2
4x −2
3
(
2x+1
)
a+b
a
b
Apply the fraction rule:
=
+
c
c
c
2
2
4x −2
4x
2
=
3
3
3
(
2x+1
)
(
2x+1
)
(
2x+1
)
2
4x
2
=
3
3
(
2x+1
)
(
2x+1
)
2
4x
2
=
dx
3
3
(
2x+1
)
(
2x+1
)
Apply the Sum Rule: ∫f(x) ± g(x)dx = ∫f(x)dx ± ∫g(x)dx
2
4x
2
=
dx − ∫
dx
(
2x+1
) 3
(
2x+1
) 3
Hide Steps
2
(
2
4x
x
1
1
))
dx = 4
(
ln 2x + 1
|
|
+ 8
(
) 3
− 4 2x+1
(
+ 2x+1
2x+1
) 2

(

2

4x

2x+1

) 3

dx

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

= 4 ·

(

2

x

2x+1

) 3

dx

Apply Integration By Parts: uv' = uv u'v

Hide Steps

' = u v − ∫ u ' v Hide Steps 2 1 1 u =
2 1 1 u = x , u' = 2x, v' = , v =
2
1
1
u = x
, u' = 2x,
v' =
,
v = − 4
(
2x+1
) 3
(
2x+1
) 2
2
u
= x
1
v'
= =
(
2x+1
) 3
Hide Steps
d
(
2 )
u' = dx x
= 2x
d
(
2 )
x
dx
d
(
a )
a−1
Apply the Power Rule:
x
= a·x
dx
2−1
=
2x
Simplify
=
2x
Hide Steps
1
1
v = ∫
dx
= − 4
(
2x+1
) 3
(
2x+1
) 2

(

1

2x+1

) 3

dx

(

Apply Integral Substitution: f g

(

x

u = 2x + 1 du = 2dx

))

·g

' (

x dx = f u du,

)

(

)

(

u = g x

)

Hide Steps

( x dx = ∫ f u du , ) ( ) ( u = g

Substitute: u = 2x + 1

du

dx

= 2

Hide Steps

d

dx

(

2x + 1

)

Apply the Sum/Di erence Rule: (f ± g) = f ± g

d

= dx

(

2x

)

+

d

dx

(

1

)

= f ′ ± g ′ d = dx ( 2 x ) + d dx

Hide Steps

Hide Steps

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

d

dx

(2x) = 2

d

dx

(

2x

)

Take the constant out:

(a·f)

= a·f

=

d

2 dx

(

x

)

Apply the common derivative:

d

dx

(x) = 1

= 2 ·

1

Simplify

= 2

d

dx

(1) = 0

Hide Steps

d

dx

(

1

)

Derivative of a constant:

d

dx

(a) = 0

= 0

dx ( 1 ) Derivative of a constant : d d x ( a ) =

= 2 + 0

Simplify

= 2

du = 2dx

1

dx = 2 du

=

 

1

1

du

 
 

·

(

 

u

) 3

2

 

1

1

1

Hide Steps

 

·

=

(

u

) 3

2

2u

3

1

1

 

·

 

u

3

 

2

3 1 1   ·   u 3   2 Multiply fractions : a · c

Multiply fractions:

a·c

a · d = b·d

b

c

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

= 4

=

1· 1

·

u

3

2

Re ne

=

1

2u

3

=

1

2u

3

du

=

1

2u

3

du

Take the constant out:

a·f(x)dx = a·f(x)dx

=

1

2

1

·u

3

du

1

u

3

= u

−3

=

1

2

−3

·u du

Apply the Power Rule:

a+1

xdx = a+1 ,

a

x

a ≠ −1

1

= 2

−3+1

u

· −3+1

Substitute back u = 2x + 1

1

= ·

(

2x+1

) −3+1

2 −3+1

Simplify

=

1

4 2x+1

(

) 2

Add a constant to the solution

=

1

4 2x+1

(

) 2

+ C

(

x

2 (

1

4 2x+1

(

) 2 )

2x

(

1

4 2x+1

(

) 2 )

dx

)

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

=

4

(

2

x

4 2x+1

(

) 2

2

(

x

2x+1

) 2

dx

)

Take the constant out:

a·f(x)dx = a·f(x)dx

=

4

(

2

x

4 2x+1

(

) 2

(

1

2

·

(

x

2x+1

) 2

dx

))

(

Apply Integral Substitution: f g

u = 2x + 1

du = 2dx

(

x

))

' (

·g x dx = f u du, u = g x

)

(

)

(

)

Hide Steps

( · g x dx = ∫ f u du , u = g x )

Substitute: u = 2x + 1

du

dx

= 2

Hide Steps

d

dx

(

2x + 1

)

Apply the Sum/Di erence Rule:

(f ± g) = f ± g

d

= dx

(

2x

)

+

d

dx

(

1

)

= f ± g ′ ′ ′ d = dx ( 2 x ) + d

d

(2x) = 2

   

Hide Steps

Hide Steps

dx

 
 

d

 

)

 

dx

(

2x

 

Take the constant out:

(a·f)

= a·f

 

=

d

2 dx

(

x

)

   

d

(x) = 1

 

Apply the common derivative:

dx

 

=

2 ·

1

Simplify

 
 

=

2

 

d

   

Hide Steps

Hide Steps

dx

(1) = 0

 
 

d

1 )

 

dx

(

Derivative of a constant:

d

dx

(a) = 0

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

= 0

= 2 + 0

Simplify

= 2

du = 2dx

1

dx = 2 du

x 1 = ∫ · du ( u ) 2 2 Hide Steps x 1
x
1
=
·
du
(
u
) 2
2
Hide Steps
x
1
x
·
=
(
u
) 2
2
2
2u
x
1
·
2
2
u
c
a·c
Multiply fractions:
b a · d = b·d
x· 1
=
2
u
·
2
Re ne
x
=
2
2u
x
=
du
2
∫ 2u
u−1
u = 2x + 1 ⇒
x =
2
u− 1
=
2
du
2
2u
Hide Steps
u− 1

2

2u

2

u−1

=

4u

2

u− 1

2

2u

2

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

Apply the fraction rule:

=

u−1

2· 2u

2

b

c

b

a = c·a

Multiply the numbers: 2 · 2 = 4

u−1

=

4u

2

=

u−1 du

4u

2

=

4

(

2

x

4 2x+1

(

) 2

(

1

2

·

u−1 du

4u

2

))

Take the constant out:

a·f(x)dx = a·f(x)dx

( 4 2x+1

))

 

4

x

2

(

1

1

·

u−1 du

 

=

· 4

 

(

) 2

2

u

2

   

u−1

1

1

Hide Steps

Expand

u

2

:

u

u

2

1 Hide Steps Expand u 2 : u u 2 u −1 2 u Apply the

u−1

2

u

Apply the fraction rule:

a+b =

c

a +

c

b

c

u−1 =

u

1

 

2

2

2

u

u

 

u

u

1

=

 

2

2

u

u

 

u

 

1

Hide Steps

Cancel u

2

:

u

u   1 Hide Steps Cancel u 2 : u u 2 u Cancel the common

u

2

u

Cancel the common factor: u

=

1

u

1

= u

1

u

2

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

=

4

(

2

x

4 2x+1

(

) 2

(

1

2

1

· 4

1

·u

1

u

2

du

))

Apply the Sum Rule: f(x) ± g(x)dx = f(x)dx ± g(x)dx

=

4

(

2

x

4 2x+1

(

) 2

(

1

2

1

· 4

(

1

u

1

du u du

2

)))

u

1 du = ln|u|

 

Hide Steps

1 du

 

u

 
 

Use the common integral:

u

1 du = ln

(|

u

|

)

|

= lnu

|

1

 

1

Hide Steps

u

2

du = − u

 

1

2

du

 

u

1 −2

2 = u

u

−2 = ∫ u du a+1 a x Apply the Power Rule: ∫xdx = a+1
−2
=
∫ u du
a+1
a
x
Apply the Power Rule:
∫xdx = a+1
,
a ≠ −1
−2+1
u
=
−2+1
Simplify
1
=
− u
(
2
x
(
1
1
))))
=
4
2 1 lnu −
·
(
|
|
(
(
u
4 2x+1
) 2
4
Substitute back u = 2x + 1
(
2
x
(
1
=
4
2 1 ln 2x + 1
·
(
))))
|
|
1
(
(
) 2
4
2x+1
4 2x+1

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

Simplify

(

 

2

 

4

 

x

=

4 2x+1

(

(

2

2x+1

) 3

dx

(

2

2x+1

) 3

dx

=

) 2

1

+ 8

(

|

ln 2x + 1

2

(

1

2x+1

) 2

|

1

+ 2x+1

))

Hide Steps

+ 1 − 2 ( 1 2 x +1 ) 2 | 1 + 2 x

Take the constant out:

a·f(x)dx = a·f(x)dx

= 2 ·

(

1

2x+1

) 3

dx

(

Apply Integral Substitution: f g

(

x

u = 2x + 1 du = 2dx

))

' (

·g x dx = f u du, u = g x

)

(

)

(

)

Hide Steps

( · g x dx = ∫ f u du , u = g x )

Substitute: u = 2x + 1

du

dx

= 2

Hide Steps

Substitute: u = 2 x + 1 du dx = 2 Hide Steps d dx (

d

dx

(

2x + 1

)

Apply the Sum/Di erence Rule:

(f ± g) = f ± g

d

= dx

(

2x

)

+

d

dx

(

1

)

d

dx

(2x) = 2

Hide Steps

= dx ( 2 x ) + d dx ( 1 ) d dx ( 2

d

dx

(

2x

)

Take the constant out:

(a·f)

= a·f

=

d

2 dx

(

x

)

Apply the common derivative:

d

dx

(x) = 1

= 2 ·

1

Simplify

= 2

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

d

dx

(1) = 0

Hide Steps

d

dx

(

1

)

Derivative of a constant:

d

dx

(a) = 0

= 0

dx ( 1 ) Derivative of a constant : d d x ( a ) =

= 2 + 0

Simplify

= 2

du = 2dx

1

dx = 2 du

=

(

1

u

) 3

·

1

2

du

(

1

u

) 3

·

1

2

=

1

2u

3

Hide Steps

1 1

·

3 2

u

Multiply fractions:

=

1· 1

·

u

3

2

a·c

b

a · d = b·d

c

Re ne

=

1

2u

3

=

1

2u

3

du

d = b · d c Re ne = 1 2 u 3 = 1 ∫

1

= 2 ·2u

3

du

Take the constant out:

1

= 2 · 2

1

·u

3

du

a·f(x)dx = a·f(x)dx

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

1

3

u

=

= u

1

2 · 2

−3

−3

·u du

Apply the Power Rule:

a+1

xdx = a+1 ,

a

x

a ≠ −1

1

= 2 · 2

−3+1

u

· −3+1

Substitute back u = 2x + 1

=

2 ·

1

·

(

2x+1

) −3+1

 

2

−3+1

Simplify

 

1

 

=

 

(

2 2x+1

) 2

=

4

(

x

2

(

4 2x+1

) 2

1

(

+ ln 2x + 1

8

|

|

1

+ 2x+1

))

(

1

2 2x+1

(

) 2 )

Simplify

 

=

4

(

x

2

(

4 2x+1

) 2

1

(

+ ln 2x + 1

8

|

|

1

+ 2x+1

))

+

1

(

2 2x+1

) 2

Add a constant to the solution

 

=

4

(

x

2

(

4 2x+1

) 2

+

1

8

(

|

ln 2x + 1

|

1

+ 2x+1

))

+

1

(

2 2x+1

) 2

+ C

6/19/2017

integral(4x^2­2)/((2x+1)^3)dx­IndefiniteIntegralCalculator­Symbolab

Graph

Plotting:

(

2

4x −2

2x+1

) 3

Graph Plotting: ( 2 4 x −2 2 x +1 ) 3